2018
DOI: 10.1097/shk.0000000000001080
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Downregulates Biomarkers of Sepsis Via Inhibition of Proteasome's Proteases

Abstract: Lipopolysaccharide (LPS) is the main agonist of gram-negative bacteria and initiates inflammation. We recently reported that plasmas from sepsis patients revealed increased levels of following group of biomarkers; VCAM-1, ICAM1, CRP, resistin, and proteasome LMP subunits. Our objective here was to compare effects of resveratrol (shown to be a nonspecific proteasome inhibitor by us) and a known LMP7 inhibitor (ONX-0914, specific inhibitor) on proteasome's activities, as well as on inflammatory markers mentioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
18
0
2
Order By: Relevance
“…*p , 0.05, **p , 0.01. the pan IP inhibitor LU-005i did not increase cell death of CD11c + , CD11b + , NK1.1 + , CD19 + , CD4 + , and CD8 + after 24 h (27). Silswal et al (54) showed that treatment of THP-1 cells, a human monocytic leukemia cell line, with 250 nM ONX 0914 resulted in autophagy and vacuole accumulation. In addition, no increase in poly(ADP-ribose) polymerase cleavage was observed in ONX 0914-treated TCR-activated mouse or human CD4 cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…*p , 0.05, **p , 0.01. the pan IP inhibitor LU-005i did not increase cell death of CD11c + , CD11b + , NK1.1 + , CD19 + , CD4 + , and CD8 + after 24 h (27). Silswal et al (54) showed that treatment of THP-1 cells, a human monocytic leukemia cell line, with 250 nM ONX 0914 resulted in autophagy and vacuole accumulation. In addition, no increase in poly(ADP-ribose) polymerase cleavage was observed in ONX 0914-treated TCR-activated mouse or human CD4 cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, PAMPs induce a “cytokine storm” of pro-inflammatory mediators, which drive the local intestinal and systemic inflammation (32). The released mediators can lead to an upregulation of endothelial adhesion molecules (e.g., ICAM, VCAM, E-, and P-selectin), resulting in increased recruitment of neutrophils and monocytes and in turn to increased levels of pro-inflammatory cytokines and ROS (34, 35). These cellular responses aggravate vasodilatation and induce a high level of capillary leakage with the development of interstitial edema.…”
Section: Introductionmentioning
confidence: 99%
“…Cerqueira et al (54) reported that resveratrol significantly reduced the production of ROS, intercellular adhesion molecule 1 (ICAM-1), human β-defensin-2 and cell surface Fas receptor, inhibited caspase-3 and -7 activation, and upregulated glutathione peroxidase expression in a Pseudomonas aeruginosa-induced A549 cell injury model. Silswal et al (55) reported that resveratrol inhibited expression of inflammatory factors in LPS-induced human cluster of differentiation (CD)14 + monocytes, including of vascular cell adhesion molecule 1, ICAM1, C-reactive protein and resistin, and activity of proteasome subunit low-molecular-weight protein 7. Other studies have shown that resveratrol inhibited the phosphorylation of NF-κB-p65 and the expression of inflammatory factors in human THP-1 cells following LPS induction (37,56).…”
Section: Discussionmentioning
confidence: 99%